2019
DOI: 10.1002/jso.25621
|View full text |Cite
|
Sign up to set email alerts
|

Frequent rectal gastrointestinal stromal tumor recurrences in the imatinib era: Retrospective analysis of an International Patient Registry

Abstract: Introduction: Rectal gastrointestinal stromal tumor (GIST) is rare and comprises about 3% of GIST. Methods: Registry data was collected by the Life Raft Group June 1976 to November 2017. All patients had a histologic GIST diagnosis. Demographic, clinicopathologic, and clinical outcome data were patient reported. Recurrence-free survival (RFS) was analyzed using the Kaplan-Meier method and Cox regression analysis.Results: Of 1798 patients in the database, 48 had localized rectal GIST (2.7%).Patients were freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 21 publications
3
15
0
Order By: Relevance
“…Tumors with KIT mutations accounted for 93.9% of all the rectal GIST. In the current study, all tumors detected harbored KIT mutations, 82.6% in Exon 11, 13.0% in Exon 9, and 4.4% in Exon 13, and was almost consistent with that of Stuart et al's16 …”
supporting
confidence: 90%
“…Tumors with KIT mutations accounted for 93.9% of all the rectal GIST. In the current study, all tumors detected harbored KIT mutations, 82.6% in Exon 11, 13.0% in Exon 9, and 4.4% in Exon 13, and was almost consistent with that of Stuart et al's16 …”
supporting
confidence: 90%
“…A higher grade in the Miettinen risk score has also been associated with lower survival rates. 5 14 24 25 In fact, in a retrospective study conducted by Sakin et al, 8 the Kaplan-Meier analysis showed a significantly lower DFS ( p = 0.034) and OS ( p = 0.022) in high-risk patients, compared with their non-high-risk counterparts. Moreover, a study published in 2019 8 reported that high-risk score negatively affected DFS (HR = 5.158; 95% CI 1.418–12.750; p = 0.013).…”
Section: Resultsmentioning
confidence: 98%
“…According to most reports in the literature, older age is considered a poor prognostic factor. 10 14 24 32 33 Additionally, male gender, 9 34 hematochezia at diagnosis, and tumor rupture during surgery 9 34 35 are also clinical predictors of prognosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, 5‐year OS was higher than 95%. Finally, Stuart et al 23 have shown that adjuvant therapy with imatinib is associated with improved DFS.…”
Section: Discussionmentioning
confidence: 99%